Urban-rural Disparities in Trends of Pulmonary Hypertension-Related Mortality in the United States, 2004-2019 (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Hospital Medicine; Research